Perbaikan Sistem Pergudangan PT. X - Erwin Istanto Jaya (Jurnal Titra, 2018)
PT.X is a private limited company which is operating in the furnishing sector. The company has a 22 meters x 45 meters warehouse located in Citraland that is used to store the imported good’s before reselling them to the customers. Current condition of the warehouse has caused some problems to occur which include the inefficiency of the product searching process and the discrepancy of the bookkeeping archives. The non-existence of a specified layout and Standard Operating Procedure (SOP) of the warehouse storage system are the roots of these problems. Thus, establishing a proposal that aims for improving the warehouse storage system is essential to tackle the problems. The output of this research is a proposed warehousing system, consisting of procurement system, storage system, good’s preparation system, and good’s delivery system. Data that are needed for this research are the list of demands, list of purchases, product’s dimensions, and product characteristics. The layout improvement hopefully can facilitate warehouse operators in taking the good’s and other activities. The layout improvement is done by putting the good’s based on the largest flow. Additional improvements such as SOPs, defective criteria standards, and company documents improvement are expected to create a better documentation system, in order to reduce the occurrence of recording errors and good’s damage.